Self-adaptive and secure mechanism for IoT based multimedia services: a survey - Singh, Irish; Lee, Seok Won (Multimedia Tools and Applications, 2022)
With the advent of internet of things (IoT) and IoT multimedia services in real-time applications, including smart healthcare, smart home, and smart connected transportation, IoT multimedia systems have significantly enhanced the lifestyle. However, the increased number of connected heterogeneous IoT multimedia devices have resulted in several vulnerabilities and cyberattacks. The existing multimedia in IoT multimedia security solutions are insufficient for detecting such complex attacks and require a self-adaptive security mechanism that can monitor the changing environment and detect, mitigate, plan, and prevent future prospective attacks in real time. In this study, we conduct a study of several self-adaptive security approaches for IoT multimedia and analyze them based on critical, security metrics to determine their level of support and the achieved satisfaction for IoT multimedia services. The evaluation results show significant insights, challenges, and concerns in the existing approaches, which can provide vital information for the development of future IoT multimedia security research. We propose a self-adaptive security model for IoT multimedia and discuss a case utilizing a mobile e-health system, where we use an adaptation model (using monitor-analyze-plan-execute over a shared knowledge adaptation loop) to determine the adaptation requirement based on the confidence level of several security factors. The adaptation requirement depicts that adaptation is required for stabilizing the security factors in a continuous context-changing sustainable e-health IoT multimedia environment.
Keywords: Adaptation requirements; Changing environment; Internet of Things (IOT); Knowledge adaptations; Multimedia environment; Multimedia security; Real-time application; Self adaptive securities; Mobile eHealth; Multimedia in IoT; Non-functional requirements; Self-adaptive security